Convergence Theorems for Infinite Family of Multivalued Quasi-Nonexpansive Mappings in Uniformly Convex Banach Spaces - Aunyarat Bunyawat; Suthep Suantai (Abstract and Applied Analysis)
We introduce an iterative method for finding a common fixed point of a countable family of multivalued quasi-nonexpansive mapping Ti in a uniformly convex Banach space. We prove that under certain control conditions, the iterative sequence generated by our method is an approximating fixed point sequence of each Ti. Some strong convergence theorems of the proposed method are also obtained for the following cases: all Ti are continuous and one of Ti is hemicompact, and the domain K is compact.